Crystallographic and magnetic structure of SrCoO2.5 brownmillerite: Neutron study coupled with band-structure calculations - Muñoz, Angel (2008)
A study of the crystallographic and magnetic structure of SrCoO2.5 with a brownmillerite-type structure has been carried out from neutron powder-diffraction (NPD) measurements at temperatures ranging from 10 to 623 K, across the Néel temperature (TN =537K) of this antiferromagnetic oxide. The study has been complemented with differential scanning calorimeter (DSC), dc susceptibility and magnetization measurements. Although the refinement of the crystal structure from NPD data is possible in the orthorhombic Pnma and Ima2 space groups, the support of ab-initio band-structure calculations has allowed us to select, without ambiguity, the Ima2 space group as the ground state for SrCoO2.5 brownmillerite. In Ima2 the crystallographic structure of SrCoO2.5 is described as layers of corner-sharing Co1 O6 octahedra alternating along the a axis with layers of vertex-sharing Co2 O4 tetrahedra, conforming chains running along the [0 0 1] direction. The magnetic structure below TN =537K is G -type with the magnetic moments directed along the c axis. This magnetic arrangement is stable from TN down to 10 K. At T=10K, the magnetic moment values for Co1 and Co2 atoms are 3.12 (13) μB and 2.88 (14) μB, respectively, compatible with a Co2+ L state, where L stands for a ligand hole. The magnetic susceptibility curves show, below 200 K, a divergence of zero-field cooling and field cooling curves, displaying broad maxima which are interpreted as due to the presence of ferromagnetic clusters embedded into an antiferromagnetic matrix. These inhomogeneities are inherent to the synthesis process, by quenching microcrystalline samples of SrCoO3-x composition from high temperature, where cubic, ferromagnetic perovskites have been identified by diffraction methods.